Governing pregnancy in South Africa: political and health debate, policy and procedures - Du Plessis, Ulandi (Rhodes University, Faculty of Humanities, Institute of Social and Economic Research, 2019)
South Africa democratised in 1994. However, due to the discriminatory and segregationist character of the preceding regime, vast swathes of the country's spaces and people entered the democratic period heavily deprived of essential government services. This was the case with health care in general, including maternal health care. There were also little to no national data available on maternal deaths, especially among the black population. One of the first tasks of the new National Department of Health (NDoH) was to target the high maternal mortality rate. The NDoH made maternal deaths notifiable by law and instituted auditing and information gathering systems in the health sector; health infrastructure was expanded exponentially, and maternal health care was made free. Despite this, the last 24 years have seen the maternal mortality escalate. The latest statistics show that between 1200 and 1300 women die in the South African public health sector each year during pregnancy and the puerperium. This puts the current institutional maternal mortality rate (MMR) at around 154/100 000 live births. The international target for 'developing' countries was to reduce the MMR rate by three quarters by 2015, which would have meant a reduction to 38/100 000 live births. The aim of this dissertation is to examine how the democratic South African government (influenced heavily by global health thinking) has laboured to reduce that statistic. I analyse, using Foucauldian discourse analysis, all relevant health and maternal health policies, procedural documents and reports produced by and for the NDoH in the last 24 years. I draw on Foucauldian concepts, specifically those related to Foucault's work on governmentality. In this dissertation I introduce a new perspective towards the maternal health practices implemented in South Africa, practices that have generally remained unquestioned, been perceived as self-evident, and thus often escaping critical analysis. Through an analysis of the intended operation of the public antenatal clinic (within the larger institutional system) I show how 'development' has come to operate as a truth regime in South Africa "“ facilitating the introduction of liberal governmentality (including some advanced liberal practices) into public health service provision.
Keywords: South Africa. Department of Health (1994- ); Maternal health services -- South Africa; Mothers -- Mortality -- South Africa; Prenatal care -- South Africa; African mothers -- Mortality -- South Africa